BOOK REVIEW: Gabriella Erdélyi, (ed.), “Érzelmek és mostohák. Mozaik családok a régi Magyarországon (1500-1850)” [“Emotions and stepparents. Blended families in Old-Hungary”], Budapest: HAS, Institute of History of the Research Centre for the Humanities, 2019 - FEHÉR, Andrea (Studia Universitatis Babeș-Bolyai Historia, 2019)
The history of family has been discussed over and over from different perspectives by social and cultural historians, who seemed to be much preoccupied, especially regarding the late medieval and early modern times, with aspects such as continuity and change in family life. Emotions were of course present in this debate, and discussed mostly in the same terms, being perceived either as learned or innate. What was not, however, often discussed, is the importance of these feelings in much complicated (although quite common) family structures, such as stepfamilies. Remarriage or living in a blended family are aspects which received little attention. Therefore, this volume addresses a significant gap in the history of the early modern family. Since some chapters focus more heavily on emotions, the edited collection is not just a contribution to the history of the Hungarian family, but also to the study of emotional behavior, too. The book is the fourth volume of the Momentum “Integrating Families” Research Group lead by Gabriella Erdélyi.